Current status of orchard mechanization technologies and key development priorities in the 15th Five-Year Plan period - Mei, Song; He, Jing; Lyu, Xiaolan; Song, Zhiyu; Cao, Guangqiao; Shen, Cheng (International Journal of Agricultural and Biological Engineering, 2025)
Orchard mechanization technologies are a key driver of progress in the fruit industry. Their advancement enhances operational efficiency, reduces labor intensity, and minimizes the waste of agricultural inputs. This study reviewed the current regional status of orchard mechanization in China and introduced advanced technologies for mechanized orchard production. The whole mechanized production technology for orchard was analyzed across four core dimensions, including digital orchard scenario reconstruction, autonomous navigation, under-canopy mechanized operations, and tree-oriented mechanization technologies. Furthermore, a comparative analysis was conducted on cutting-edge technologies used in similar types of equipment across four critical operational stages (power platforms, weeding, plant protection, and harvesting), and their respective advantages and limitations in various application contexts were also analyzed. Then, several key problems hindering further development were identified, including limited standardization for mechanization compatibility, significant equipment shortages in hilly and mountainous areas, insufficient integration of advanced technologies into orchard machinery, an aging and undereducated rural workforce, and an underdeveloped system of socially-supported agricultural machinery services. Finally, in view of these problems, six strategic development priorities for the orchard mechanization in the 15th five-year plan period were put forward, including promoting the integration of standardized orchard construction and agricultural machinery systems, overcoming bottlenecks of mechanized equipment, upgrading intelligent equipment in gentle slope orchards, strengthening the application of intelligent technologies in modern standardized orchards, attracting and training highly educated fruit professionals, and strengthening the construction of socialized agricultural machinery service systems. Key words: orchard mechanization; intelligent; production management; main problems; development focusDOI: 10.25165/j.ijabe.20251806.9314Citation: Mei S, He J, Lyu X, Song Z Y, Cao G Q, Shen C. Current status of orchard mechanization technologies and key development priorities in the 15th Five-Year Plan period. Int J Agric & Biol Eng, 2025; 18(6): 12–23.